2009
DOI: 10.1016/j.cej.2009.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Biosorptive performance of an Escherichia coli biofilm supported on zeolite NaY for the removal of Cr(VI), Cd(II), Fe(III) and Ni(II)

Abstract: a b s t r a c tOne of the major environmental concerns of nowadays is the presence of heavy metals in industrial effluents. Aiming a solution for this problem, various efforts have been made towards research and implementation of economic and easily adaptable processes to remove heavy metals. The ability of a biofilm of Escherichia coli supported on NaY zeolite to biosorb Cr(VI), Cd(II), Fe(III) and Ni(II) was investigated in batch experiments aiming the treatment of wastewater with low metal concentrations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…A large microorganism accumulation in both the interior of the ruggedness and in the superficial zones of natural zeolite was observed during bioreactor operation. The attachment and colonization of SRB cells on the zeolite surface caused they were more protected from friction [38]. It was also observed that the support surface formed by a compact mass of microorganisms, principally with coccoid and bacillary forms.…”
Section: Characteristics Of Developed Srb Biofilms Populationmentioning
confidence: 73%
“…A large microorganism accumulation in both the interior of the ruggedness and in the superficial zones of natural zeolite was observed during bioreactor operation. The attachment and colonization of SRB cells on the zeolite surface caused they were more protected from friction [38]. It was also observed that the support surface formed by a compact mass of microorganisms, principally with coccoid and bacillary forms.…”
Section: Characteristics Of Developed Srb Biofilms Populationmentioning
confidence: 73%
“…In recent years, bacteria species supported materials have been used as alternative material. Arthrobacter viscosus supported granular activated carbon and NaY, Escherichia coli supported granular activated carbon, kaolin and NaY zeolite are used in the Cr(VI) removal [36][37][38][39][40][41]. It has been found that the affinities of granular activated carbon, kaolin and NaY zeolite were improved by the attachment of bacteria species on the material surface.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease of biomass was observed after 10 days of growth due to the decrease of nutrients in the medium. Growth of biomass in spite of xenobiotic conditions has been reported in a study by Quintelas et al (2009) in which they observed growth of E. coli on NaY zeolite.…”
Section: Characteristics Of Zeolite-p Simplicissimum Biomassmentioning
confidence: 87%
“…However, the large scale implementation of in situ attenuation and remediation schemes remains to be extensively explored. Several studies on bioremediation have been reported (Chen et al, 2005;Kumar et al, 2011;Pazos et al, 2010;Quintelas et al, 2009;Zhang et al, 2011). The structural polymers in the cell walls of microorganisms contain functional groups such as carboxyl (COO − ), phosphoryl (R-PO 3 ) and amino (RN-H) groups that largely influence adsorption (Kulczycki et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation